Thermal properties of water-ethylene glycol based hybrid Al2O3-SiO2 nanofluids in PEMFC cooling plate / Muhammad Syafiq Idris - Idris, Muhammad Syafiq (2022)
Proton Electrolyte Membrane fuel cell (PEMFC) is seen as one of the viable alternative energies to internal combustion engine (ICE) due to the clean product bypass. However, the performance of PEMFC needs to be optimized through excellent thermal management. The main duty of thermal management system is to maintain the desirable temperature with a uniform temperature distribution across the stack and individual membranes.